Sedimentology and geochronology of the fossil bearing upper member of Malapa site in the Cradle of Humankind (South Africa, Johannesburg) - Maphanda, Dakalo Portia (University of the Witwatersrand, Johannesburg, 2023)
Malapa is a palaeoanthropological site in the Cradle of Humankind in South Africa. It is known for preserving two partial skeletons of Australopithecus sediba. These skeletons are encased in Pleistocene cave deposits that are subdivided into six sedimentary facies i.e., A-F. There are two pits exposed at the site i.e., the main pit (pit 1) and pit 2. Sedimentary facies A-E are deposits from the main pit, and facies F occurs in both pit 1 and 2. Pit 2 deposits were previously classified as a homogenous deposit of facies F. Recent excavation campaigns carried out in 2019 and 2020 exposed new deposits adjacent to the deposits in pit 2. The purpose of this study was to enhance the geological understanding of the deposits at Malapa by investigating the newly exposed deposits. We found that facies F deposits are not as homogenous as previously thought, based on grain size, textural variation, and general appearance of the deposit. The newly exposed deposits and facies F were collectively called the upper member as they entail the deposits investigated in this study. Facies F and the newly exposed deposits were then targeted for sampling to investigate the petrography of the deposits. The study also investigated the stratigraphic position of the upper member in relation to facies A-F from the main pit by attempting to resolve an age of the deposits. The study utilized a sedimentary analysis approach by combining petrographic descriptions, mainly SEM-EDS and XRF to confirm the existence of multiple facies in the upper member. The results show that the upper member comprises facies B, C, F and a newly defined facies G. Facies G contains more chert and quartz clasts than any facies described in the previous studies. It only has calcite in the form of a micrite matrix supporting chert, quartz, or Mn-Fe-coated grains. Considering that the six facies from previous studies are chronologically well constrained, the age of facies G was also investigated. Two flowstones were used to estimate the maximum age of the clastic sediments. Flowstone 2 was situated between the clastic sediments of facies B, C and F so it represents a maximum age for sediments below it and the minimum age for those above it. Flowstone 2 is the same as the Flowstone 2 sampled by a previous study where it returned a well-constrained age of 2.06 ± 0.021 Ma. Flowstone 3 was determined to be a clast that could have collapsed from the cave roof and was situated in previously unstudied sediments. The sediments were determined to be Facies C deposits close to Pit 1. We attempted to date Flowstone 2 by U-Pb LA-ICP-MS but attained an age of 3.72 ± 0.77 Ma (Pliocene in age), inconsistent with previous dating and unrealistic in the context of the Malapa. Flowstone 3 produced a U-Pb age of 7.50 ± 0.37 Ma (Miocene in age). The U-Pb flowstone ages have large errors. Flowstone 2 has an error of ~21% of the age and flowstone 3 has an error of ~5%. Both flowstone ages have too large an error to be considered useful to constrain the age of the upper member. A second dating approach was then used on the clastic sediments themselves using cosmogenic nuclide burial dating. The method yielded more well-constrained ages of 1.59 ± 0.44 Ma. This is an isochron burial age that suggests that the upper member is much younger than the deposits in the main pit, but the isochron burial age is in agreement with the literature U-Pb ages from the flowstones. This is because 1.59 + 0.44 = 2.03 Ma which coincide with the U-Pb ages of the flowstones in the main pit and pit 2. The age of the samples from facies G have an average age of 1.52 ± 0.088 Ma which makes facies G the youngest in stratigraphy.
A dissertation submitted in fulfillment of the requirements for the degree of Master of Science (Palaeontology in Geology), to the Faculty of Science, School of Geosciences, at the University of the Witwatersrand, Johannesburg, 2023.
Keywords: Malapa; Speleothems; Cave; Sedimentology; Australopithecus; Sediba; UCTD; SDG-15: Life on land